1999
DOI: 10.1146/annurev.biochem.68.1.649
|View full text |Cite
|
Sign up to set email alerts
|

MCM Proteins in DNA Replication

Abstract: The MCM proteins are essential replication initiation factors originally identified as proteins required for minichromosome maintenance in Saccharomyces cerevisiae. The best known among them are a family of six structurally related proteins, MCM2-7, which are evolutionally conserved in all eukaryotes. The MCM2-7 proteins form a hexameric complex. This complex is a key component of the prereplication complex that assembles at replication origins during early G1 phase. New evidence suggests that the MCM2-7 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
478
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 583 publications
(492 citation statements)
references
References 190 publications
12
478
1
1
Order By: Relevance
“…But there is also evidence that the six eukaryotic MCMs can form a heterohexamer even when not associated with the chromatin (Ref. 48; our unpublished observations). If such a hexameric (or dodecameric) form of the MCMs were recruited to the origins, the ring would have to be momentarily open to engage the DNA (Fig.…”
Section: (C) Dpb11 Sld and Psf Genesmentioning
confidence: 70%
See 2 more Smart Citations
“…But there is also evidence that the six eukaryotic MCMs can form a heterohexamer even when not associated with the chromatin (Ref. 48; our unpublished observations). If such a hexameric (or dodecameric) form of the MCMs were recruited to the origins, the ring would have to be momentarily open to engage the DNA (Fig.…”
Section: (C) Dpb11 Sld and Psf Genesmentioning
confidence: 70%
“…3A). This model seems plausible because MCM proteins form different subcomplexes in vivo, (48) and the binding of Xenopus Mcm2, Mcm4 and Figure 2. Possible mechanisms of replicative helicase action.…”
Section: (C) Dpb11 Sld and Psf Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptide sequence data were obtained from purified p62 xPARN by mass spectrometry (see Fig+ 3 for peptide positions)+ As previously reported, these peptides were highly homologous to the human poly(A) ribonuclease (hPARN) amino acid sequence (Korner et al+, 1998)+ Taking advantage of this similarity, an hPARN cDNA probe was used to screen a Xenopus oocyte cDNA library at low stringency+ A 1+53-kb clone was obtained that was 75% identical to the 59 coding region of the human cDNA, but which lacked the 39 portion and did not contain an in-frame stop codon+ To obtain a fulllength clone, the partial sequence was used to screen a Xenopus kidney l ZAP II cDNA library+ Two clones were obtained from this library from a screen of ;600,000 plaques+ The larger of the clones (2 kb) overlapped the original clone and contained all of the coding region except for the first 16 nt+ The predicted molecular weight of full-length xPARN is 72+8 kDa+ The deduced amino acid sequences for xPARN and hPARN are shown in Figure 3+ Although the two proteins share 72% overall identity, there is significantly more heterogeneity in the C-terminal region than elsewhere, suggesting a possible divergence of function+ No other proteins of known function are similar to human or Xenopus PARN, but related hypothetical proteins from several species (Arabidopsis thaliana, Schizosaccharomyces pombe, and Caenorhabditis elegans) are present in the nonredundant database+ In addition to the conserved tripartite RNase D exonuclease domains (Korner et al+, 1998), xPARN also contains motifs that were not reported for the human enzyme+ One of these is a region that is similar to a functionally undefined domain conserved among helicases known as minichromosome maintenance proteins (MCM; amino acids 132-152)+ Although the conserved region falls outside the Walker A and Walker B motifs known to be required for nucleotide binding, other conserved regions, which may confer nucleotide specificity, have not been characterized (Tye, 1999)+ The xPARN sequence also contains a putative RNA recognition motif (RRM; amino acids 446-502) that may contribute to its poly(A)-binding activity (Siomi & Dreyfuss, 1997)+ …”
Section: Cloning Of the Xparn Cdnamentioning
confidence: 99%
“…The MCM2-7 proteins form a hexameric complex that assembles at replication origins during early G1 phase [20]. Coordination of the functional interactions between the MCM2-7 proteins and other components of the pre-RC is mediated by CDKs [19,21]. Subsequently, loading of DNA polymerase occurs and is mediated by the replication factor complex (RFC) [22].…”
Section: Introductionmentioning
confidence: 99%